Prognostic factors of the developmental outcome in neonates after hypoxic ischemic encephalopathy - Kawes Omer Zangana; Sana Abdulrazzaq Ibrahim (Advanced Medical Journal)
Background and objective: The objectives of this study were to identify the etiologic profile and neurodevelopmental outcome of hypoxic-ischemic encephalopathy, and determine the usefulness of brain imaging to predict neurodevelopmental outcome.